PENINGKATAN KETUNTASAN HASIL BELAJAR SISWA PADA MATERI POKOK KEMAGNETAN MELALUI PENERAPAN MODEL GENERATIVE LEARNING DI KELAS IX-2 SMP NEGERI 2 TIGAPANAH TAHUN PELAJARAN 2018/2019 - Limar Hutabalin (Universitas Negeri Medan, 2021)
Abstract: This study aims to determine the improvement of student learning outcomes and activity mastery by applying a generative learning model to the subject matter of magnetism in class IX-2 of SMP Negeri 2 Tigapanah in the 2018/2019 school year. This research is a classroom action research with two cycles. The place of research is SMP Negeri 2 Tigapanah with the subjects in the study are all students of class IX-2 SMP Negeri 2 Tigapanah for the 2018/2019 academic year, totaling 26 students. In the study, learning outcomes data were obtained through formative tests while student learning activity data were obtained through observations in teaching and learning activities (KBM). The results of this study indicate; 1) the mastery of student learning outcomes increased by applying the generative learning model, as evidenced by the students' test results, learning mastery increased by 19%. In Cycle I the average test score was 74 with learning completeness of 69% and in Cycle II the average test score was 81 with learning completeness up to 88%, and succeeded in providing classical learning outcomes; 2) student learning activities increased by applying the generative learning model, as evidenced by the results of observations from Cycle I to Cycle II, the activity of paying attention to the teacher's explanation increased from 61.18% to 88.53%, the activity of discussing subject matter increased from 54.41% to 87.65%, the activity of making observations rose from 53.38% to 87.94%, the activity of asking the teacher rose from 61.76% to 90.74% and the activity of making summaries increased from 46.32% to 88.68% . All activities have achieved success indicators in Cycle II.Keywords: Generative Learning, Learning Outcomes, MagnetismAbstrak: Penelitian ini bertujuan untuk mengetahui peningkatan ketuntasan hasil dan aktivitas belajar siswa dengan menerapkan model generative learning pada materi pokok kemagnetan di kelas IX-2 SMP Negeri 2 Tigapanah tahun pelajaran 2018/2019. Penelitian ini adalah penelitian tindakan kelas dengan dua siklus. Tempat penelitian adalah SMP Negeri 2 Tigapanah dengan subjek dalam penelitian adalah seluruh siswa kelas IX-2 SMP Negeri 2 Tigapanah tahun pelajaran 2018/2019 yang berjumlah 26 siswa. Dalam penelitian, data hasil belajar diperoleh melalui tes formatif sedangkan data aktivitas belajar siswa diperoleh melalui observasi dalam kegiatan belajar mengajar (KBM). Hasil penelitian ini menunjukkan; 1) ketuntasan hasil belajar siswa meningkat dengan menerapkan model generative learning, terbukti dari hasil tes siswa ketuntasan pembelajaran naik sebesar 19%. Pada Siklus I rata-rata nilai tes 74 dengan ketuntasan pembelajaran sebesar 69% dan pada Siklus II rata-rata nilai tes 81 dengan ketuntasan pembelajaran naik menjadi 88%, dan berhasil memberikan ketuntasan hasil belajar secara klasikal; 2) aktivitas belajar siswa meningkat dengan menerapkan model generative learning, terbukti dari hasil observasi dari Siklus I ke Siklus II, aktivitas memperhatikan penjelasan guru naik dari 61,18% menjadi 88,53%, aktivitas mendiskusikan materi pelajaran naik dari 54,41% menjadi 87,65%, aktivitas melakukan pengamatan naik dari 53,38% menjadi 87,94%, aktivitas bertanya pada guru naik dari 61,76% menjadi 90,74% dan aktivitas membuat rangkuman naik dari 46,32% menjadi 88,68%. Seluruh aktivitas telah mencapai indikator keberhasilan pada Siklus II.Kata Kunci : Generative Learning, Hasil Belajar, Kemagnetan